UPAYA NORMALISASI HUBUNGAN JEPANG DAN KOREA SELATAN MELALUI MEKANISME KERJASAMA KEAMANAN PERIODE 2021-2022 - Fitriyanti, Rahmi; Saubil Navira, Aurora (Lintas Cendekia Publishing, 2024)
Japan and South Korea have traces of disharmonious relations since after Japan won the war with Russia in the period February 1904-September 1905 and the war between China and Japan in August 1894-April 1895. The relationship between the two was exacerbated by the disputed conflict on the islands of Dokdo and Takeshima. Therefore, during the reigns of Shinzo Abe and Moon Jae-in, efforts were made to normalize relations, which was marked by the formation of the Treaty on Basic Relations between Japan and the Republic of Korea. In the midst of normalization efforts, the Shinzo Abe administration, relations have become tense again due to Japan's conservative policy of tightening the export of chemicals from South Korea's semiconductor industry. This fact is a challenge for security cooperation between the two countries to worsen. This was responded by Fumio Kishida and Yoon Suk Yeol by joining the US through trilateral security cooperation. This article is analyzed using two concepts, namely, the concept of defense diplomacy and the concept of national security. The research method used through a qualitative approach is descriptive and explanatory. The results found that efforts to normalize relations between the two countries through the security cooperation mechanism turned out to be more focused on strengthening the military by forming an alliance with the United States (US).